The Analysis of Articles Related to Curriculum and Instruction Field in Educational Researcher Journal (2005 - 2016) - Tas, Ilkay Dogan; Yetkiner, Alper; Ince, Murat (European Scientific Journal, ESJ, 2017)
The purpose of this study is to reveal the research tendencies in the articles related to curriculum and instruction published in Educational Researcher Journal during the last ten years (2005-2016). Descriptive survey model and document analysis were used to conduct the study. A content analysis approach was used to analyse the data obtained. By making general evaluation in the analysed articles according to their subjects, research design and methods, data collection tools, sampling types, genders of the researchers and the publishing years of the articles, the tendency in this field was aimed to be determined. As a result of the study, it was revealed that the subjects of the articles are mostly related to instruction levels curriculum, tendencies in education, teacher training, education reform, and teaching approaches. The main research design used in this article is the literature review. The research method used is qualitative, and the document analysis was employed as a data collection tool.